DWI reversibility in acute ischemic stroke due to basilar artery occlusion following successful recanalization - Launhardt, Niclas; Jesser, Jessica; Hasan, Dimah; May, Rebecca; Nikoubashman, Omid; Wiesmann, Martin; Nguyen, Thanh N.; Möhlenbruch, Markus Alfred; Kernbach, Julius; Weyland, Charlotte S. (Clinical neuroradiology, 2025)
Diffusion Weighted Imaging (DWI) represents the infarct core in acute ischemic stroke. DWI reversibility is a phenomenon reported for the anterior circulation affecting small brain areas of the white matter. This study aims to define DWI reversibility in the posterior circulation after successful recanalization of basilar artery occlusion (BAO) and its influence on patient outcome.